2017
DOI: 10.1038/icb.2016.128
|View full text |Cite
|
Sign up to set email alerts
|

CAR T‐cell therapy of solid tumors

Abstract: The potential for immunotherapy as a treatment option for cancer is clear from remarkable responses of some leukemia patients to adoptive cell transfer using autologous T cells genetically modified to express chimeric antigen receptors (CARs). However, the vast majority of cancers, in particular the more common solid cancers, such as those of the breast, colon and lung, fail to respond significantly to infusions of CAR T cells. Solid cancers present some formidable barriers to adoptive cell transfer, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
156
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(156 citation statements)
references
References 65 publications
0
156
0
Order By: Relevance
“…Consequently, in principle, CAR therapy is restricted to targeting cell surface molecules uniquely expressed by tumor cells or those that are only expressed by dispensable normal tissues (Kakarla and Gottschalk, 2014). Due to a lack of such targets (Klebanoff et al, 2016), and perhaps a number of other factors that are incompletely elucidated (Yong et al, 2017), CAR therapy has shown extremely limited efficacy against solid tumors.…”
Section: Principles Of Immunotherapy To Treat Human Cancermentioning
confidence: 99%
“…Consequently, in principle, CAR therapy is restricted to targeting cell surface molecules uniquely expressed by tumor cells or those that are only expressed by dispensable normal tissues (Kakarla and Gottschalk, 2014). Due to a lack of such targets (Klebanoff et al, 2016), and perhaps a number of other factors that are incompletely elucidated (Yong et al, 2017), CAR therapy has shown extremely limited efficacy against solid tumors.…”
Section: Principles Of Immunotherapy To Treat Human Cancermentioning
confidence: 99%
“…As there are several excellent reviews summarizing the recent information about clinical trials in the field of CAR-T 2023 , we will omit the detailed description of clinical trial data in this review, to avoid duplication.…”
Section: Car Design and Therapeutic Efficacymentioning
confidence: 99%
“…Other obstacles to optimal CAR-T cell function are related to tumor microenvironment and include lack of chemotactic homing signals, lack of costimulatory molecules for T-cells, abnormal tumor vasculature and immunesuppressive cells. [111] Approaches to overcome obstacles to anti-GD2 CAR T-cell activity against neuroblastoma include incorporation of costimulatory molecules such as 4–1BB[112] and combination with PD-1 blockade. [113] The expansion of T-cell subpopulations such as CD4+ cells or central memory cells transfected with CAR is also being investigated.…”
Section: Preclinical Approachesmentioning
confidence: 99%